2002
DOI: 10.1103/physrevlett.88.042504
|View full text |Cite
|
Sign up to set email alerts
|

Renormalization of the Hartree-Fock-Bogoliubov Equations in the Case of a Zero Range Pairing Interaction

Abstract: We introduce a natural and simple way to implement the regularization scheme of the Hartree-Fock-Bogoliubov equations with zero range pairing interaction. The renormalization scheme proves to be equivalent to a simple energy cutoff with a position dependent running coupling constant.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
266
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 190 publications
(272 citation statements)
references
References 22 publications
(50 reference statements)
3
266
0
Order By: Relevance
“…The reason is that the δ-function interaction is singular in the pairing channel and so must be regularized (see, e. g. Ref. [56]). Here we do so by cutting off the single-quasiparticle spectrum.…”
Section: B N -And Z-dependencementioning
confidence: 99%
“…The reason is that the δ-function interaction is singular in the pairing channel and so must be regularized (see, e. g. Ref. [56]). Here we do so by cutting off the single-quasiparticle spectrum.…”
Section: B N -And Z-dependencementioning
confidence: 99%
“…Whereas vortices are well understood both in the BEC and the BCS limits, it is not clear how the characteristics of the vortex (such as the core size) behave in the crossover regime. Bulgac and Yu have extended density functional theory to superfluid fermion systems [4], and studied vortex states in the BCS regime within their superfluid local density approximation (SLDA) [5]. They found that in the BCS regime vortices give rise to a depletion in the fermion density.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the bare coupling constant in the pairing channel could in principle have some intrinsic density dependence and such dependence has been considered by various authors during the years [2,[6][7][8][9]13]. Secondly, the renormalization of the pairing interaction, as described in our recent work [3][4][5], leads to position dependence as well. The equations for the quasi-particle wave functions u i (r) and v i (r) and related quantities are…”
mentioning
confidence: 99%
“…The argument that nuclear forces have a finite-range is superfluous, see Refs. [3][4][5], since nuclear pairing phenomena are manifest at small energies and distances of the order of the coherence length, which is larger than nuclear radii.We shall consider local nuclear EDFs only (which depend on various densities, as opposed to an explicit dependence on the full density matrix), as they proved overwhelmingly successful in describing normal nuclear properties. It is natural to expect that the same should apply to pairing properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation